Leadership Competency Formation in Management Students Using Mobile Learning Technologies - Alexandrovna Pogrebinskaya, Ekaterina (2021)
The focus of education on world standards predetermines the need to modernize the forms, methods, and means of teaching taking into account the current level of development of Internet technologies and information communications. Mobile learning reflects the educational trends most fully as it provides continuous access to information at any time. It should be noted that the development of mobile technologies makes portable mobile devices more usable and universal. With the development of mobile technologies, the need for quick access to information and the acquisition of knowledge has increased, as well as the mobility of the population. Therefore, the search for new approaches in organizing the educational process and creating educational materials accounting for the preferences of modern students and the information society as a whole becomes especially urgent. The goal of the study is to reveal the experience of implementing mobile learning based on the example of teaching the “Fundamentals of Leadership” course. Based on an experimental study, the study of the influence of the use of mobile learning technologies on the formation of leadership competency in management students is carried out.